PENERAPAN METODE GRAMMAR TRANSLATION METHOD (GTM) PADA GURU BAHASA INGGRIS DI SMP NEGERI GUDANG ARANG - Dina Mariana Tarigan; Seli Marlina Radja Leba (Musamus University, 2022)
The implementation of this community service activity aims to make SMP Gudang Arang students able to understand and know English as a foreign language and provide an understanding of English Learning Methods that are useful for increasing students' interest, willingness and interest in learning English vocabulary and grammar. This service activity was carried out at the SMP Gudang Arang in September 2021, while the population consisted of 20 class VII students of SMP Gudang Arang. There are two methods of implementing this activity, namely training and mentoring. The training materials are divided into two, namely Exposure to Materials on tips to become successful English learners and Application of the Grammar Translation Method (GTM) in English while Mentoring is assisting teachers in implementing the GTM method so that students are interested in learning English. The results of this training showed that most of the students who were involved in English vocabulary and grammar training activities experienced an increase in their ability and motivation to learn English. In addition, an increase in students' motivation and interest in learning was also seen during this training activity. This is indicated by their active involvement in every learning activity and their enthusiasm in carrying out each task given. In mentoring in learning English vocabulary and grammar there are some students who have good English skills. Some of these students can pronounce English vocabulary and English grammar with correct pronunciation, students also tend to be active, students' English learning outcomes are also quite good